(untitled) (Archive of Conferences, 2020)
The article discusses the various functions of the application in the social networks "Telegram", "Facebook", "Odnoklassniki" and computer texts, "discourse parameters" that provide access to various resources: video, audio and text formats, as well as features of virtual discourse. Oral, written and virtual forms of discourse were also analyzed